Electrospun F18 Bioactive Glass/PCL—Poly (ε-caprolactone)—Membrane for Guided Tissue Regeneration - Hidalgo Pitaluga, Lucas (Materials (Basel), 2018)
Barrier membranes that are used for guided tissue regeneration (GTR) therapy usually lack bioactivity and the capability to promote new bone tissue formation. However, the incorporation of an osteogenic agent into polymeric membranes seems to be the most assertive strategy to enhance their regenerative potential. Here, the manufacturing of composite electrospun membranes made of poly (ε-caprolactone) (PCL) and particles of a novel bioactive glass composition (F18) is described. The membranes were mechanically and biologically tested with tensile strength tests and tissue culture with MG-63 osteoblast-like cell line, respectively. The PCL-F18 composite membranes demonstrated no increased cytotoxicity and an enhanced osteogenic potential when compared to pure PCL membranes. Moreover, the addition of the bioactive phase increased the membrane tensile strength. These preliminary results suggested that these new membranes can be a strong candidate for small bone injuries treatment by GTR technique.